APOE and AGT in the Finnish p.Arg133Cys CADASIL population. (26th March 2015) - Siitonen, M.; Mykkänen, K.; Pescini, F.; Rovio, S.; Kääriäinen, H.; Baumann, M.; Pöyhönen, M.; Viitanen, M.
<x xml:space="preserve">Abstract</x> Background CADASIL is an inherited systemic small vessel disease, the affected status of brain vessels leading to subcortical vascular dementia. The defective gene is NOTCH3 in which over 230 different pathogenic mutations have been identified. The clinical course of CADASIL is highly variable even within families. Previous studies have shown that additional genetic factors modify the phenotype. Aims and methods Altogether, 134 Finnish CADASIL patients with p.Arg133Cys mutation were analysed for possible associations between the apolipoprotein E (APOE) genotype, angiotensinogen (AGT) p.Met268Thr polymorphism or neutral p.Ala202Ala NOTCH3 polymorphism and earlier first‐ever stroke or migraine. Results We found no association between the APOE genotypes, AGT polymorphism, NOTCH3 polymorphism and earlier first‐ever stroke or migraine. Conclusions The APOE, AGT and NOTCH3 polymorphism did not modify the onset of strokes or migraine in our CADASIL sample, which is one of the largest mutationally homogenous CADASIL populations published to date. International collaboration, pooled analyses and genomewide approaches are warranted to identify the genetic factors that modify the highly variable CADASIL phenotype.